A traffic-aware quality-of-service control mechanism for software-defined networking-based virtualized networks - Jiameng Shi; Sang-Hwa Chung (International Journal of Distributed Sensor Networks)
Network virtualization technology allows the creation of virtual networks that reflect the requirements of various services and distribute resources of a physical network among virtual tenants. Recently, the virtualization of physical networks through software-defined networking technology has become a popular method. OpenVirteX is a software-defined networking-based network virtualization platform that can create multiple virtual and programmable networks on top of a single physical infrastructure and provide full isolation of each virtual tenant. However, some shortcomings persist in OpenVirteX, one of which is the lack of a mechanism to distribute physical network resources efficiently among the virtual tenants. In this article, we propose a novel quality-of-service management mechanism, based on the single rate three color marker proposed by the Internet Engineering Task Force. This mechanism employs two new token buckets, called global token buckets, which are used to collect idle tokens from each virtual network. Furthermore, a resource manager can redistribute the collected tokens among the virtual networks according to their weights. Finally, our work achieves a maximum improvement of approximately 1.6 times over the performances of previous mechanisms.